Forecasting Room Occupancy Rates in Batu City: Implicationsfor Government Policy Using ARIMA Method - Putri, Clarissa Rexana; Prabudhi, Safandra Alifia; Putranto, FX Gugus Febri; Astasia, Adina; Tjahjo, Thomas Wunang (PANGRIPTA, 2024)
This study utilizes the Autoregressive Integrated Moving Average (ARIMA) to forecast the Room Occupancy Rate (ROR) for both Star Hotels and Non-Star Hotels in Batu City throughout 2024. Data from 2018 to 2023, sourced from the Central Statistics Agency, informs the analysis. The results indicate a gradual decline in room occupancy rates across both star and non-star hotels. These findings hold significant implications for decision-making within the tourism sector, offering insights to enhance tourist attraction and stimulate economic development in Batu City. By anticipating future trends in room occupancy, stakeholders can strategize effectively, potentially adjusting marketing approaches, infrastructure investments, or tourism policies to address the observed decline. This study contributes valuable information to guide policy interventions aimed at sustaining tourism vitality and fostering economic growth in Batu City.